High-precision satellite orbit propagation with estimation of the covariance matrix - А.Г. Есенгалиев; А.Б. Муканов (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2022)
In this paper is proposed to use a model of high-precision propagation of the satellite position, in which the disturbing accelerations are determined, and the obtained numerical results are presented. All disturbing forces acting on the satellite are modeled, the up-to-date data of the parameters of the atmospheric drag model, as well as the parameters IERS, EOP are used. The developed software for satellite orbit propagation is applicable to support the flight control of the satellite, while ensuring the accuracy of the level of 10-15 meters along the position vector of the satellite over a weekly time interval. With a given model of satellite motion and known statistical characteristics of orbit determination errors, the covariance matrix is predicted along with the state vector, which has found application in many applied tasks for support of Flight dynamics activities.